Conceptual Analysis in the Contemporary Educational Landscape - Winchester, Ian; Manery, Robert (Philosophical Inquiry in Education, 2019)
This introduction to a special issue on the value of conceptual analysis provides a historical context and reasons for continuing to engage and value conceptual analysis in the contemporary educational landscape.